Thinking blocks: Solving fraction problems involving higher order thinking skills - Zainal Abidin, Nur Liyana (Serials Publications, 2017)
A fraction is a complex topic in mathematics. Some literature indicates that students made mistakes in solving mathematical problems involving higher order thinking skills which are related to Number domain. The Number domain includes Whole Numbers, Sequences and Patterns of Numbers, Fractions, Decimals, Percentages and Integers. Therefore, this study was conducted to determine the effectiveness of Thinking Blocks in order to help students solve fraction problems involving higher order thinking skills. By incorporating a pre-post quasi-experimental design, students were divided into two groups. The experimental group (n = 32) were exposed to treatment to improve higher order thinking skills. Whereas, the other group acted as a control group (n = 22) and were taught in a conventional way. Samples involved in this study were Form One students in Johor. The instrument used in identifying the level of higher order thinking skills consists of twelve higher order thinking questions. The gathered data were then analyzed using inferential statistics. The finding of this study revealed that to the control group the experimental group showed a statistically significant improvement on higher order thinking skills group compared. As a conclusion, if teachers consistently practice the strategies of higher order thinking, there is a high chance to develop and nurture higher order thinking skills among students when learning Fractions.